Uterine fibroids — why you should choose tailored therapies based on the joint decision of the physician and the patient - Michal Ciebiera; Tomasz Lozinski; Ayman Al-Hendy (Ginekologia Polska)
Uterine fibroids (UFs) are the most common benign tumors of the myometrium, affecting up to 70% women by age 50. Although many cases remain asymptomatic, symptomatic UFs can significantly reduce quality of life through excessive bleeding, anemia, pelvic pain, infertility, and obstetric complications. Despite the availability of various conservative treatments — including pharmacotherapy, uterine artery embolization, and ultrasound thermoablation — surgical interventions, particularly hysterectomy, remain the dominant approach in many countries. This discrepancy between evidence-based recommendations and routine practice highlights the persistence of a paternalistic model of care, where patients are often excluded from treatment decisions and not informed about alternatives. Emerging concepts such as shared decision making (SDM) and personalized therapy emphasize the need to adapt treatment plans to each woman’s clinical profile, reproductive goals, and preferences. SDM fosters trust, better adherence to therapy, and improved acceptance of complications by actively involving patients in choosing their care. The development of modern pharmacological options, like GnRH analogs, further expands possibilities for effective, reversible, fertility-preserving treatments. A paradigm shift toward patient-centered, individualized management is essential to address ethical challenges, reduce unnecessary hysterectomies, and improve outcomes. Implementing SDM and expanding access to conservative therapies require systemic changes in reimbursement, training, and patient education to ensure that care focuses not only on the disease but on the woman as a whole.